Welding C-Mn steels using the pulsed current MIG welding process - Foote, W. J. (Cranfield University, 1986)
The welding of C-Mn steels using the pulsed current MIG welding process was investigated. Following initial work on the basic fusion characteristics, the process was applied to the production of closed butt joint linepipe welding and narrow gap welding (in the flat and H-V positions). The initial stage of the work covered the determination of pulse parameters for controlled metal transfer with a variety of wires and shielding gases. Basic bead-on-plate fusion characteristics were investigated 1n all welding positions and quantified in terms of the major welding variables of current and travel speed. Welding position was shown to have no effect on fusion behaviour. Successful full penetration closed butt root welds were produced in all welding positions. Heat input was shown to be the factor controlling bead dimensions. Close control over welding parameters are needed to maintain consistent bead sizes. Complete joint simulations were also made. The vertical-up technique was shown to give superior fusion characteristics with the process producing excellent quality results in all positions. Narrow gap MIG welding was shown to be feasible without wire manipulation at gap widths below 12 mm in the flat position. A wire manipulation technique gave excellent fusion characteristics with gap widths greater than 12 mm. A computer program was devised as a guide to the selection of process parameters and possible fusion behaviour. Modelling considerations showed that H-V position narrow gap welding would be feasible only with gap widths less than 10 ... A short experimental programme validated the predictions of fusion behaviour by the model and indicated the direction for future development work.